Pengaruh Perencanaan Pembelajaran Berbasis Proyek dan Motivasi Belajar terhadap Kemampuan Berpikir Kritis Mahasiswa - Gita Febrina Samosir; Ambarita, Charles Fransiscus; Adelia Apulisa (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the influence of project-based learning planning and learning motivation on students' critical thinking skills. The study used a quantitative approach with a correlational design and involved 101 students from several study programs at Medan State University. Data were obtained through a Likert-scale questionnaire that had been tested for validity and reliability, with Cronbach's Alpha values ​​of 0.916 for learning planning, 0.868 for learning motivation, and 0.926 for critical thinking skills, respectively. All data were then analyzed through classical assumption tests, including normality, multicollinearity, and simple and multiple regression analyses. The results showed that project-based learning planning had a positive and significant effect on students' critical thinking skills, indicated by a regression coefficient of 0.412 with a significance of 0.000. Learning motivation also had a significant positive effect with a coefficient of 0.507 and a significance of 0.000, and had a stronger contribution than learning planning. Simultaneously, both variables had a significant effect on critical thinking skills, evidenced by an F value of 71.025 with a significance of 0.000. This research model was able to explain 63.1% of the variation in students' critical thinking skills. This finding emphasizes the importance of quality learning planning and optimal learning motivation in fostering the development of higher-order thinking skills.